BS ISO/IEC 23200-2. Information technology. Radio frequency identification for item management. Part 2. Interference rejection performance test method between an Interrogator as defined in ISO/IEC 18000-63 and a heterogeneous wireless system (10th January 2022) - British Standards Institution,
No abstract available